2007
DOI: 10.1098/rsbl.2007.0191
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory receptor gene repertoires in secondary-adapted marine vertebrates: evidence for reduction of the functional proportions in cetaceans

Abstract: An olfactory receptor (OR) multigene family is responsible for the well-developed sense of smell possessed by terrestrial tetrapods. Mammalian OR genes had diverged greatly in the terrestrial environment after the fish-tetrapod split, indicating their importance to land habitation. In this study, we analysed OR genes of marine tetrapods (minke whale Balaenoptera acutorostrata, dwarf sperm whale Kogia sima, Dall's porpoise Phocoenoides dalli, Steller's sea lion Eumetopias jubatus and loggerhead sea turtle Caret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 16 publications
5
107
4
1
Order By: Relevance
“…Functional olfactory receptor gene repertoires were reduced independently in the multiple origins of aquatic mammals (Niimura, 2009). Semiaquatic mammals, on the other hand, have variably maintained their olfactory receptor genes and olfactory structures (Kishida et al, 2007). For instance, while Trichechus manatus (West Indian manatee) displays evidence of a rudimentary olfactory system (Mackay-Sim et al, 1985), seals have a main olfactory bulb and an accessory olfactory bulb associated with a vomeronasal organ (Freitag et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional olfactory receptor gene repertoires were reduced independently in the multiple origins of aquatic mammals (Niimura, 2009). Semiaquatic mammals, on the other hand, have variably maintained their olfactory receptor genes and olfactory structures (Kishida et al, 2007). For instance, while Trichechus manatus (West Indian manatee) displays evidence of a rudimentary olfactory system (Mackay-Sim et al, 1985), seals have a main olfactory bulb and an accessory olfactory bulb associated with a vomeronasal organ (Freitag et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Members of the order Cetacea either have rudimentary olfactory systems, or lack an olfactory system altogether (Tyack, 2000). Kishida et al (2007) demonstrated that members of Cetacea, including the dwarf sperm whale (Kogia sima), Dall's porpoise (Phocoenoides dalli), and the Minke whale (Balaenoptera acutorostrata) all have a significantly higher number of non-functional olfactory receptor pseudogenes than their close terrestrial relatives. This suggests a diminished role of olfaction, as the number of pseudogenes is inversely proportional to olfactory functionality.…”
Section: Olfactory Systems or Lack Thereofmentioning
confidence: 99%
“…Some studies have tried to infer causalities, for example the loss of olfactory GPCR [95] in response to the advent of trichromatic vision in primates [96]. Large scale degeneration of olfactory GPCR genes is found in cetaceans (dolphins, whales), which have secondarily adapted to a marine habitat and have lost or greatly reduced their sense of smell acquired in terrestrial environments [97]. Taken together, using phylogenetic data, it is difficult to prove how variation of a gene has generated an evolutionary advantage under certain environmental circumstances.…”
Section: Signatures Of Selectionmentioning
confidence: 99%
“…In bowhead whales (Balaena mysticetus), a complex olfactory bulb and olfactory tracts are present and more than half of the OR genes are intact, suggesting a potentially functional sense of smell (Thewissen et al, 2011;Kishida et al, 2015a). However, OR genes are reported to be functionally reduced by pseudogenization in Odontoceti (Kishida et al, 2007). Bottlenose dolphins possess only two class I and ten class II OR genes that are intact, as well as a single vomeronasal receptor type 1 gene (Kishida et al, 2015b).…”
Section: Anatomical Data On Olfactionmentioning
confidence: 99%